Uji Aktivitas Ekstrak Kulit Buah Beberapa Tanaman dan Daya Hambatnya Terhadap Pertumbuhan Ralstonia Solanacearum pada Cabai - SHEILA SIMANJUNTAK; MADE SRITAMIN; I KETUT SUADA (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana, 2014)
ABSTRACT Inhibiting Ability of Some Fruit Rinds Extract Against the Growth of Ralstonia solanacearum on Chili Ralstonia solanacearum infect plant root through wound that occured indirectly. The symptoms of the disease are whole plant to wilt, the leaves turn yellow to blackish-brown, and eventually the plant dies. In the culture media contained Triphenyltetrazolium Chloride (TZC) the bacterium tend to form white colony and irregular round shape. The method used to determine the extract activating was well diffusion method. The results of the study showed that application of coconut rind extract inhibited the bacterium. The minimum concentration was 1,25% with diameter of inhibition zone was 15 mm. The phenolic compounds contained on the coconut rind was possibly inhibit the growth of the bacterial colonies. Further research needs to be conducted in vivo to determine the effectiveness of antibacterial compounds contained in the extract of coconut rind. Keyword: fruit rind extract, Ralstonia solanacearum, well diffusion method